2022
DOI: 10.3390/plants11131674
|View full text |Cite
|
Sign up to set email alerts
|

Biopriming of Maize Seeds with a Novel Bacterial Strain SH-6 to Enhance Drought Tolerance in South Korea

Abstract: Maize is the third most common cereal crop worldwide, after rice and wheat, and plays a vital role in preventing global hunger crises. Approximately 50% of global crop yields are reduced by drought stress. Bacteria as biostimulants for biopriming can improve yield and enhance sustainable food production. Further, seed biopriming stimulates plant defense mechanisms. In this study, we isolated bacteria from the rhizosphere of Artemisia plants from Pohang beach, Daegu, South Korea. Twenty-three isolates were isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…For example, biopriming of maize seeds with GA-producing bacterial strains showed markedly enhanced maize seedling tolerance to oxidative stress. This also improved drought tolerance by up to 20% ( Shaffique et al., 2022 ). When the rhizobacterium Azospirillum brasilense was introduced to the roots of Arabidopsis, the host plant displayed increased endogenous abscisic acid (ABA) levels and drought tolerance ( Eichmann et al., 2021 ).…”
Section: Specialized Metabolites Production By Phytomicrobiome – a Tr...mentioning
confidence: 98%
“…For example, biopriming of maize seeds with GA-producing bacterial strains showed markedly enhanced maize seedling tolerance to oxidative stress. This also improved drought tolerance by up to 20% ( Shaffique et al., 2022 ). When the rhizobacterium Azospirillum brasilense was introduced to the roots of Arabidopsis, the host plant displayed increased endogenous abscisic acid (ABA) levels and drought tolerance ( Eichmann et al., 2021 ).…”
Section: Specialized Metabolites Production By Phytomicrobiome – a Tr...mentioning
confidence: 98%
“…Bioprimed plants exhibit robust and rapid defence responses against different abiotic stresses. Shaffique et al 86 reported that biopriming with Enterobacter ludwigii stimulated defence response in maize (Z. mays L.) plants under water-deficit stress conditions resulting in drought tolerance and enhanced germination percentage of maize (Z. mays L.) seedlings. Priming with T. harzianum and Phanerochaete chrysosporium enhanced defence enzymes activities to alleviate salinity stress induced oxidative damage in soybean (G. max L.) and wheat (T. aestivum L.) plants, respectively.…”
Section: Mitigation Of Biotic Stresses In Plantsmentioning
confidence: 99%
“…Bioprimed plants exhibit robust and rapid defence responses against different abiotic stresses. Shaffique et al 86 . reported that biopriming with Enterobacter ludwigii stimulated defence response in maize ( Z. mays L.) plants under water‐deficit stress conditions resulting in drought tolerance and enhanced germination percentage of maize ( Z. mays L.) seedlings.…”
Section: Biopriming‐mediated Stress Resilience In Plantsmentioning
confidence: 99%
“…The beneficial effects of seed priming on a variety of crops have been confirmed. [1][2][3][4] Although priming, as a plant-growth enhancement technique, can be applied at many stages in the developmental cycle of a plant, seed treatment is popular due to its practicality and simplicity.…”
Section: Introductionmentioning
confidence: 99%